North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition Position Paper: Plant-based Milks. Issue 2 (August 2020) - Merritt, Russell J.; Fleet, Sarah E.; Fifi, Amanda; Jump, Candi; Schwartz, Sally; Sentongo, Timothy; Duro, Debora; Rudolph, Jeffrey; Turner, Justine
Abstract : ABSTRACT: Parents and caretakers are increasingly feeding infants and young children plant-based "milk" (PBM) alternatives to cow milk (CM). The US Food and Drug Administration currently defines "milk" and related milk products by the product source and the inherent nutrients provided by bovine milk. Substitution of a milk that does not provide a similar nutritional profile to CM can be deleterious to a child's nutritional status, growth, and development. Milk's contribution to the protein intake of young children is especially important. For almond or rice milk, an 8 oz serving provides only about 2% or 8%, respectively, of the protein equivalent found in a serving of CM. Adverse effects from the misuse of certain plant-based beverages have been well-documented and include failure to gain weight, decreased stature, kwashiorkor, electrolyte disorders, kidney stones, and severe nutrient deficiencies including iron deficiency anemia, rickets, and scurvy. Such adverse nutritional outcomes are largely preventable. It is the position of the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition (NASPGHAN) Nutrition Committee, on behalf of the society, that only appropriate commercial infant formulas be used as alternatives to human milk in the first year of life. In young children beyond the first year of life requiring a dairy-free diet, commercial formula may be a preferable alternative to cow's milk, when such formula constitutes a substantial source of otherwise absent or reduced nutrients (eg, protein, calcium, vitamin D) in the child's restricted diet. Consumer education is required to clarify that PBMs do not represent an equivalent source of such nutrients. In this position paper, we provide specific recommendations for clinical care, labelling, and needed research relative to PBMs.